Research of Hydrogenation and Dehydrogenation Effect on the Structural and Phase State of the Titanium Alloy - Stepanova E. N. Ekaterina Nikolaevna; Sypchenko V. S. Vladimir Sergeevich; Lider A. M. Andrey Markovich; Liu G. (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen